IJNS Turns Seven-High Impact for Neonatal Screening - Ralph Fingerhut; Peter C. J. I. Schielen (MDPI AG, 2021)
Since our inaugural issue in 2015, the International Journal of Neonatal Screening (IJNS) has solidified its position as the preferred platform to publish the scientific output of the members of the International Society of Neonatal screening (ISNS) and professionals in fields related to neonatal screening [...]